Income inadequacy among creative professionals – An interplay of identity and skills - Stenholm Pekka; Hytönen Kaisa; Pukkinen Tommi; Heinonen Jarna (Denmark, 2025)
Financially challenging work of creative professionals is a widely acknowledged concern. Research has explored how working conditions and type of work affects the income, but has not addressed the influence of individual’s identity and business skills on income formation. Drawing from observations of 410 creative professionals, we investigate how identities and business skills impact income formation. Our findings show that perceived creative identity increases the chances of income inadequacy, but obtaining business skills decrease such chances. In addition, the findings suggest that perceived entrepreneurial identity accompanied with business skills decreases the likelihood of income inadequacy. Hence, our findings highlight how individuals’ identity and business skills influence individuals’ income. Therefore, we welcome ways to support the simultaneous development of individuals’ identity and business skills to alleviate the tensions between being creative and surviving financially.
21st Nordic Conference on Small Business Research: Conference Proceedings